Analisis E-Government Success Factors pada aplikasi WARGAKU: Inovasi Cerdas Penanganan Pengaduan Masyarakat di Kota Surabaya - Saskia Nisa Setiaatmitha; V. Rudy Handoko; Ghulam Maulana Ilman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the factors contributing to the success of e-government implementation through the Wargaku application as a digital-based public service innovation in the city of Surabaya. The Wargaku application is designed to facilitate the community in submitting complaints, aspirations, and service needs in a faster, more efficient, and transparent manner. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Analysis is conducted using an interactive model. The results of the study indicate that the success of the Wargaku application in supporting public complaint services is determined by five key factors: information and data, information technology, organizational and managerial aspects, legal and policy frameworks, and institutional or environmental factors. These five factors are interrelated in forming an effective and adaptive digital-based public service system. Although the application has achieved significant results with a complaint resolution rate above 90%, challenges remain, such as limited access for iOS users, technical system constraints, and the need to improve public digital literacy. This study recommends strengthening technological infrastructure, expanding cross-device accessibility, and enhancing user capacity as strategic steps to support the sustainability of local e-government.